GbAS: Group-based Authentication System for Machine to Machine (M-M) Communication - Dr. Charanjit Singh, Amandeep Singh (International Journal of Advanced Science and Technology, 2020)
Machine-to-Machine communication is an important research paradigm considered as the main foundation stone for the growth of the Internet of Things (IoT). It draws more attention due to its low power consumption but security and efficiency are the key issues nowadays. In addition, the combination of a large number of machine-to-machine devices in the IoT causes severe congestion, which poses a serious threatto the network. In this paper, a novel Group based Authentication System (GbAS)is proposed incorporating the curve fitting to enhance the security level, which also eases the signalling congestion level. The proposed framework is consistent with the third generation partnership project (3GPP) standard, which not only reduces the congestion level but also avoids the overload on the network. The experimental results conclude that the developed system enhances the security, reliability, and efficiency of the network. In order to enhance the current computation mechanism, the proposed framework is optimized by SP Line interpolation architecture for node selection for key sharing. The computational complexity, cost, signalling overhead and bandwidth consumption parameters considered to determine the effectiveness of the proposed technique.